Analisis Perilaku Verbal dan Non-Verbal dalam Kegiatan Berkomunikasi dalam Video Berbahasa Arab - Lutfiani, Yuni; Nandang, Ade (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2024)
Humans as social creatures cannot be separated from communication activities. In the actual practice of communicating a person also simultaneously practices a behavior, this behavior is divided into two verbal and non-verbal behaviors. Furthermore, in the real world the majority of people actually practice these two behaviors in their communication activities but they are not aware of it, therefore this article aims to explain verbal and nonverbal behavior both theoretically and practically by analyzing both behaviors in an Arabic video. This research uses descriptive qualitative methods in describing the data of its research results, and the data collection techniques are observation, documentation and quotation, and the data analysis technique is content analysis technique with three stages: data reduction, presentation, and conclusion drawing. The results showed that in the communication activities in the Arabic videos studied, there were 17 verbal behaviors in the form of assertive, directive, commissive, and expressive and 54 nonverbal behaviors in the form of kinestic, facial expressions, vocalic and proxemic. This data shows that in communication practice, a person actually uses more nonverbal behavior than verbal behavior. The implication of this study is that this research can be a reference for readers to understand the discussion of verbal and nonverbal behavior in communication activities both theoretically and practically, so that this understanding can be a means to improve the quality of their communication.